The Effect of Unemployment and Poverty Rates on the Human Development Index in North Sumatra from 2013–2024 - Sabrina Erisa Aulia Sihotang; Khairunnisa Umi Al Mas; Dwi Atika Zahara; Siti Mardiah (Outline Publisher, 2026)
This study analyzed the effect of unemployment and poverty on the Human Development Index in North Sumatra Province. Human development reflects the quality of life of the population through the dimensions of education, health, and a decent standard of living. However, socio-economic problems such as unemployment and poverty may influence the achievement of human development. This research employed a quantitative approach using secondary time-series data from 2013 to 2024 obtained from official publications of the Central Statistics Agency. Multiple linear regression analysis was used to examine the relationship between unemployment, poverty, and the Human Development Index. The results showed that the regression model had strong explanatory power with an Adjusted R Square value of 0.850, indicating that unemployment and poverty explained 85% of the variation in the Human Development Index. The simultaneous test showed a significant effect with an F value of 26.595 and a significance level of 0.001. Partially, unemployment did not have a significant effect on the Human Development Index with a significance value of 0.210. In contrast, poverty had a negative and significant effect with a regression coefficient of −2.594 and a significance value of 0.000. These findings indicated that poverty played a major role in determining the level of human development. Therefore, poverty reduction and improved access to education and health services are essential strategies for enhancing human development.